Effect of zinc-biofortified seeds on grain yield of wheat, rice, and common bean grown in six countries - Abdul Rashid (2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Seeds enriched with zinc (Zn) are ususally associated with better germination, more vigorous seedlings and higher yields. However, agronomic benefits of high-Zn seeds were not studied under diverse agro-climatic field conditions. This study investigated effects of low-Zn and high-Zn seeds (biofortified by foliar Zn fertilization of maternal plants under field conditions) of wheat (Tritcum aestivum L.), rice (Oryza sativa L.), and common bean (Phaseolus vulgaris L.) on seedling density, grain yield and grain Zn concentration in 31 field locations over two years in six countries. Experimental treatments were: (1) low-Zn seeds and no soil Zn fertilization (control treatment), (2) low-Zn seeds + soil Zn fertilization, and (3) Zn-biofortified seeds and no soil Zn fertilization. The wheat experiments were established in China, India, Pakistan, and Zambia, the rice experiments in China, India and Thailand, and the common bean experiment in Brazil. When compared to the control treatment, soil Zn fertilization increased wheat grain yield in all six locations in India, two locations in Pakistan and one location in China. Zinc-biofortified seeds also increased wheat grain yield in all four locations in Pakistan and four locations in India compared to the control treatment. Across all countries over 2 years, Zn-biofortified wheat seeds increased plant population by 26.8% and grain yield by 5.37%. In rice, soil Zn fertilization increased paddy yield in all four locations in India and one location in Thailand. Across all countries, paddy yield increase was 8.2% by soil Zn fertilization and 5.3% by Zn-biofortified seeds when compared to the control treatment. In common bean, soil Zn application as well as Zn-biofortified seed increased grain yield in one location in Brazil. Effects of soil Zn fertilization and high-Zn seed on grain Zn density were generally low. This study, at 31 field locations in six countries over two years, revealed that the seeds biofortfied with Zn enhanced crop productivity at many locations with different soil and environmental conditions. As high-Zn grains are a by-product of Zn biofortification, use of Zn-enriched grains as seed in the next cropping season can contribute to enhance crop productivity in a cost-effective manner.